Oil pulling and importance of traditional medicine in oral health maintenance - Naseem, Mustafa; Khiyani, Muhammad Faheem; Nauman, Hiba; Zafar, Muhammad Sohail; Shah, Altaf H; Khalil, Hesham S (International Journal of Health Sciences, 2017)
Dental diseases have detrimental effects on the functionality and quality of life of individuals. In addition, a strong relationship has been established between various oral and systemic diseases. In fact, the prevention and treatment of dental caries and periodontal disease have been shown to reduce the risk of diabetes and heart disease significantly. This goes beyond the role of oral health as a means to identify early manifestations of systemic diseases in the oral cavity. It highlights the necessity of maintaining an optimal oral hygiene to significantly modify the risk factors for serious systemic diseases. The use of oil pulling can be frequently found in ancient medical text and is supported by recent studies for its efficacy and long-term use for maintaining and improving oral health. This article provides an overview on the concept of oil pulling or oil swishing, its mechanism of action and a summary of the evidence available, which highlights the role of oil pulling in specific oral diseases. The goal of this review is to highlight the ancient procedure that has the potential to be used as an adjunct to conventional chemical means of dental plaque control, such as mouth rinses. Incorporating oil swishing as a component of daily oral hygiene can significantly improve oral and general health, specifically in lower socioeconomic groups and rural communities that may have interrupted access to health-care services and dental products such as dentifrices and mouth washes due to various factors; availability and affordability being the most important.